Load reduction instruction: Exploring a framework that assesses explicit instruction through to independent learning. (July 2018) - Martin, Andrew J.; Evans, Paul
Abstract: Load reduction instruction (LRI) is an instructional approach aimed at managing the cognitive burden on students in the initial stages of learning; then, as fluency and automaticity develop, students are encouraged to engage in guided independent learning. LRI comprises five factors: difficulty reduction, support and scaffolding, practice, feedback, and guided independence. This study examined an instrument (the Load Reduction Instruction Scale, LRIS) aimed at assessing these five factors. Among a sample of high school students from 40 classrooms, findings supported the validity of the LRIS, the conceptualising underpinning it, and its potential to guide instructional practice. Highlights: Load reduction instruction (LRI) is an approach to manage cognitive burden on students. LRI comprises: difficulty reduction, support/scaffolding, practice, feedback, independence. The Load Reduction Instruction Scale (LRIS) assesses these five factors. This study investigates the validity of the LRIS and its underlying conceptual contentions. The LRIS is a valid means of assessing the teacher's load reduction instructional approaches.